2018
DOI: 10.2147/ceor.s150900
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus intravenous iron therapy in patients with inflammatory bowel disease and iron deficiency with and without anemia in Germany – a real-world evidence analysis

Abstract: BackgroundIron-deficiency anemia and iron deficiency are common comorbidities associated with inflammatory bowel disease (IBD) resulting in impaired quality of life and high health care costs. Intravenous iron has shown clinical benefit compared to oral iron therapy.AimThis study aimed to compare health care outcomes and costs after oral vs intravenous iron treatment for IBD patients with iron deficiency or iron deficiency anemia (ID/A) in Germany.MethodsIBD patients with ID/A were identified by ICD-10-GM code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Parenteral iron is more expensive and is an additional cost to the healthcare system, which is a limiting factor in its widespread use [ 1 , 47 ]. However, further studies have shown that the long-term costs of ineffective oral iron therapy are outweighed by the immediate costs of IV iron [ 67 ]. Additionally, severe anaphylactoid reactions to HMW dextrans have previously been reported but are now increasingly rare with the newer LMW formulations [ 1 ].…”
Section: IV Ironmentioning
confidence: 99%
“…Parenteral iron is more expensive and is an additional cost to the healthcare system, which is a limiting factor in its widespread use [ 1 , 47 ]. However, further studies have shown that the long-term costs of ineffective oral iron therapy are outweighed by the immediate costs of IV iron [ 67 ]. Additionally, severe anaphylactoid reactions to HMW dextrans have previously been reported but are now increasingly rare with the newer LMW formulations [ 1 ].…”
Section: IV Ironmentioning
confidence: 99%
“…The following clinical observations may answer this question. First, IDA and FIDA frequently occur in autoimmune and inflammatory disorders such as systemic lupus erythematosus (SLE) [ 138 ], RA [ 139 , 140 ] and IBD [ 141 , 142 ]. These disorders are frequently associated with CKD, leading to ESRD [ 143 , 144 ].…”
Section: Impact Of Inflammation On Therapeutic Strategy With Iron mentioning
confidence: 99%
“…Furthermore, patients with IBD having higher levels of CRP achieved a lower Hb response with OIT than those with lower levels of CRP [ 153 ]. Thus, IIT has been more efficacious than OIT in patients with RA, SLE [ 154 , 155 ] and IBD [ 142 ]. Taken together, these data suggest that inflammation in autoimmune disorders and IBD leading to CKD/ESRD may have an impact on the expression of ferritin and hepcidin, the response to iron therapy and mode of iron therapy as well.…”
Section: Impact Of Inflammation On Therapeutic Strategy With Iron mentioning
confidence: 99%
“…The main disadvantage is the higher cost of medication and the necessity for administration by a health professional. However, a study by Stein et al [30] based in Germany found that patient outcome was better with IV iron, with fewer hospitalizations and an overall lower total health care cost as compared to oral iron. The immediate costs of IV iron may thus be offset by the long-term costs of ineffective oral iron therapy.…”
Section: Treatment Of Ida In Ibdmentioning
confidence: 99%